Is Classroom Noise Always Bad for Children? The Contribution of Age and Selective Attention to Creative Performance in Noise - Massonnié, Jessica; Rogers, Cathy Jane; Mareschal, Denis; Kirkham, Natasha Z. (Frontiers in Psychology, 2019)
Creativity is considered an important skill in learning but little is known about the environmental factors affecting it in classroom settings. Extending adult findings, this study assessed whether moderate multi-talker noise promotes children’s creativity, and whether this is moderated by children’s age, working memory, and selective attention. Forty-four elementary school children between 5 and 11 years of age, divided into younger and older age groups, participated in this within-subjects’ study. The children completed two idea generation tasks; each participant performed the task both in silence and in moderate (64dB) classroom noise. Selective attention skills, verbal and visuospatial working memory were assessed with behavioural tasks. Results showed that there were no conditions in which classroom noise promoted children’s creativity whilst some negative effects of noise were observed. Younger children (between 5 and 8 years of age) with low selective attention skills were especially at risk: they gave fewer ideas in the presence of noise, and these ideas were rated as less original. Children with good selective attention skills were globally protected against the effects of noise, performing similarly in silence and noise. Future studies about children’s specific creative strategies might help shed light on the mechanisms underlying these effects.